(untitled) (Research, Society and Development, 2021)
Environmental Education has become a great ally for raising awareness of good health practices and living with the environment. The objective of this work was to map and classify the trails existing at the Federal University of Lavras, exposing their potential to society through lectures at state and municipal schools in the city. The trails were mapped by walking using a Garmin GPS device, model GPSMAP 62 sc. Subsequently, the collected data were transferred to the Base Camp program, which has the function of tracing the route of the route, and then the data was plotted to Google Earth, providing the satellite image of the entire length of the trail. Based on the mapping of trails at the Federal University of Lavras, areas with different degrees of declivity and floristic environments are distinguished and with diverse fauna, which instigates the suggestion of trails for students according to the age group. For elementary school students I and II, the Lagoas Trail is recommended, as it has a low degree of slope, easy access, intermediate distance and recreational spots by the lagoons for fishing practices. As for high school students, the Capela Trail and the Eucalyptus Trail, as they have a more diversified environment, would be the most designated, being even conducive to the practice of adventure activities in nature. The survey and classification of these areas can contribute to future research in other projects within the University.